Parallel and digital police for new norm of public safety: from parallel security to peaceful China - WANG Fei-Yue (智能科学与技术学报)
Due to the impact of artificial intelligence generated content technologies such as AlphaGo and ChatGPT, the governance of intelligent science and technology becomes a significant concern all over the world. This review addressed related issues by integrating traditional public safety management with new artificial intelligence (AI) technologies and provided an alternative philosophy and approach for safety, security and sustainability in the future society of AI.